2020
DOI: 10.1111/dom.14076
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic fat, irrespective of ethnicity, is associated with reduced endogenous insulin clearance and hepatic insulin resistance in obese youths: A cross‐sectional and longitudinal study from the Yale Pediatric NAFLD cohort

Abstract: AimTo evaluate whether intrahepatic fat accumulation contributes to impaired insulin clearance and hepatic insulin resistance across different ethnic groups.MethodsThe intrahepatic fat content (HFF%) was quantified by magnetic resonance imaging in a multi‐ethnic cohort of 632 obese youths aged 7‐18 years at baseline and after a 2‐year follow‐up. Insulin secretion rate (ISR), endogenous insulin clearance (EIC) and hepatic insulin resistance index (HIRI) were estimated by modelling glucose, insulin and C‐peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 45 publications
3
35
1
Order By: Relevance
“…Moreover, postprandial hyperinsulinemia during an OGTT in obese NAFLD individuals has been shown to strongly correlate with reduced hepatic insulin clearance but not insulin secretion [68]. In a large cross-sectional study including 532 obese young individuals, it was shown that insulin clearance and the hepatic insulin resistance index calculated during an OGTT was~50% lower in individuals with steatosis [69].…”
Section: Liver Tg Accumulation and Systemic Hyperinsulinemia: The Effects On Insulin Clearancementioning
confidence: 99%
“…Moreover, postprandial hyperinsulinemia during an OGTT in obese NAFLD individuals has been shown to strongly correlate with reduced hepatic insulin clearance but not insulin secretion [68]. In a large cross-sectional study including 532 obese young individuals, it was shown that insulin clearance and the hepatic insulin resistance index calculated during an OGTT was~50% lower in individuals with steatosis [69].…”
Section: Liver Tg Accumulation and Systemic Hyperinsulinemia: The Effects On Insulin Clearancementioning
confidence: 99%
“…While low adiponectin concentrations appear to be an important factor, they do not entirely explain the low insulin clearance of the BA men. Low insulin clearance has been demonstrated in a wide variety of BA subjects, including healthy men [27] and women [36], obese adolescents [37] and adults with T2D [38]. The highly conserved nature of this trait is well illustrated by Osei et al who demonstrated that while African-Americans, native Ghanaians and Ghanaian immigrants to the USA have similar rates of insulin clearance to each other, all three BA groups have lower insulin clearance compared with White Americans [39].…”
Section: Discussionmentioning
confidence: 97%
“…The model as presented here is oversimplified in that it only considers glucotoxicity and neglects other factors that are likely to play a role, such as lipotoxicity (48). We are thus unable at present to address the possible role of hyperinsulinemia to promote hepatic fat accumulation (76). If prolonged, this could lead to liver damage and thus to a worsening of insulin resistance that could outlast the induced resistance we have modeled here (Eqs.…”
Section: Limitations Of the Studymentioning
confidence: 99%